Experimental Study on the Hysteresis Effect During the Counter-Current Air-water Two-phase Flow in a Hot Leg Pressurized Water Reactor" - Deendarlianto, Deendarlianto; Suhanan, Suhanan (Jurusan Teknik Mesin dan Industri, Fakultas Teknik UGM, 2010)
An investigation on hysteresis effect during the counter-current air-water two-phase flow in a hot leg pressurized water reactor has been conducted experimentally. The pattern of test section was rectangular cross section, in which it is a simplification of Konvoi nuclear reactor. The rectangular channel dimension, the length of the horizontal part and the inclination angle of the riser were (0.25x0.05) m2, 2.12 m, and 50° from horizontal plane, respectively. The onset of flooding and deflooding, was observed by analyzing the data of water levels from a vessel simulating steam generator, reactor pressure vessel and visual observation. The onset of flooding is defined as the maximum air mass flow rate at which the discharged water mass flow rate is equal to the inlet water mass flow rate. Meanwhile the onset of deflooding is defined as the maximum air mass flow rate, at which the down-flowing water mass flow rate begins to be equal to the injected water mass flow rate. As a result, it was found that (1) the occurrence of slug flow and the starting increase of the pressure drop are integral phenomena of the initial stage of the flooding during the counter-current flow of air-water in a hot leg pressurized water reactor, (2) an hysteresis effect appears on the onset of flooding, and (3) the hysteresis effect becomes more important when increasing the water mass flow rate.